Eco-health survey effort to diagnose readiness for sustainability dengue prevention and control - Nur Siyam; Bertakalswa Hermawati; Lukman Fauzi; Fahma Nur Fadila; Niken Lestari; Sifa Ul Janah; Sungatno Sungatno; Nadia Insrswari Utomo (International Journal of Public Health Science (IJPHS), 2023)
The prevention and control of dengue fever with the eco-health approach are crucial especially at the household level. However, the implementation is still limited and has continued to experience several obstacles. This study aimed to analyze the eco-health-based dengue vector control at the household level, identify the factors influencing decision-making, and assess household readiness towards the implementation. The study was conducted in Bandarharjo Village, the coastal area of Semarang City and the samples were residents who had settled for at least six months, selected using the purposive sampling technique. Furthermore, the household survey used a mixed method with quantitative and qualitative approaches. Data were collected through a Google Form, which consists of a questionnaire, an observation checklist by respondents, and interview guidelines with open- ended answer questions. The data were further analyzed with Univariate Analysis and qualitative data were processed with the Uwe Flick method. The results showed that the majority or 65.1% of the community is ready to carry out prevention and control with the eco-health method as indicated by the excellent and good readiness criteria of 14.7% and 50.5% respectively. Social capital and support from stakeholders, as well as community leaders, were found to strengthen community readiness for sustainable eco-health prevention and control of dengue fever.